2012
DOI: 10.1088/0004-637x/746/1/61
|View full text |Cite
|
Sign up to set email alerts
|

On the Progenitors of Galactic Novae

Abstract: Of the approximately 400 known Galactic classical novae, only ten of them, the recurrent novae, have been seen to erupt more than once. At least eight of these recurrents are known to harbor evolved secondary stars, rather than the main sequence secondaries typical in classical novae. In this paper, we propose a new nova classification system, based solely on the evolutionary state of the secondary, and not (like the current schemes) based on the properties of the outbursts. Using archival optical and near-inf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
126
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(139 citation statements)
references
References 50 publications
(38 reference statements)
8
126
0
Order By: Relevance
“…Mróz et al (2015) determined an orbital period of P = 1.59230(5) days using data from the OGLE survey, and suggest that the system likely contains a subgiant secondary and a massive white dwarf. This is a relatively unusual part of nova-progenitor parameter space, with only a few such systems known (Darnley et al 2012). Mróz et al (2015) additionally observed eclipses in the quiescent optical light curve, indicating that the inclination is close to 90 • (Mróz et al 2015).…”
Section: Introductionmentioning
confidence: 89%
“…Mróz et al (2015) determined an orbital period of P = 1.59230(5) days using data from the OGLE survey, and suggest that the system likely contains a subgiant secondary and a massive white dwarf. This is a relatively unusual part of nova-progenitor parameter space, with only a few such systems known (Darnley et al 2012). Mróz et al (2015) additionally observed eclipses in the quiescent optical light curve, indicating that the inclination is close to 90 • (Mróz et al 2015).…”
Section: Introductionmentioning
confidence: 89%
“…The shorter recurrence periods are driven by a combination of a high-mass WD and a high mass accretion rate. Such high accretion rates are typically driven by an evolved companion star, such as a Roche lobe overflowing sub-giant star (SG-novae; also the U Scorpii type of RNe) or the stellar wind from a red giant companion (RG-novae: symbiotic novae, or the RS Ophiuchi type RNe; see Darnley et al 2012Darnley et al , 2014a, for recent reviews).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the class of persistent SSS, classical novae (CNe) have frequently been observed to emit an SSS spectrum during the later phase of their outburst. It is now commonly accepted that SSS emission originates in binary systems containing a white dwarf primary that hosts nuclear burning of material that is accreted from a secondary star; see van den Heuvel et al (1992) and Kahabka & van den Heuvel (1997), as well as Darnley et al (2012) for discussion of types and the role of the secondary star in nova systems. In persistent SSS, the burning rate is roughly the same as the accretion rate (van den Heuvel et al 1992;Kahabka & van den Heuvel 1997), while in novae during outburst, the burning rate is higher, eventually leading the SSS emission to disappear once all hydrogen is consumed.…”
Section: Introductionmentioning
confidence: 99%